Persistent transgene expression in peripheral tissues one year post intravenous and intramuscular administration of AAV vectors containing the alphaherpesvirus latency-associated promoter 2 - Maturana, Carola J.; Engel, Esteban A. (Frontiers in Virology, 2024)
Significant progress has been made in enhancing recombinant adeno-associated virus (rAAV) for clinical investigation. Despite its versatility as a gene delivery platform, the inherent packaging constraint of 4.7 kb imposes restrictions on the range of diseases it can address. In this context, we present findings of an exceptionally compact and long-term promoter that facilitates the expression of larger genes compared to conventional promoters. This compact promoter originated from the genome of the alphaherpesvirus pseudorabies virus, latency-associated promoter 2 (LAP2, 404 bp). Promoter driving an mCherry reporter was packaged into single strand (ss) AAV8 and AAV9 vectors and injected into adult C57BL/6 mice at a dose of 5 x 1011 vg/mouse by single intravenous or intramuscular administration. An ssAAV8 and ssAAV9 vector with elongation factor-1α promoter (EF1α, 1264 bp) was injected side-by-side for comparison. After 400 days, we sacrificed the mice and examined mCherry expression in liver, kidney, heart, lung, spleen, pancreas, skeletal muscle, and brain. We found that LAP2 exhibited robust transgene expression across a wide range of cells and tissues comparable to the larger EF1α, which is currently recognized as a rather potent and ubiquitous promoter. The AAV8-LAP2 and AAV9-LAP2 constructs displayed strong transduction and transcription in liver, kidney, and skeletal muscle on both route of administration. However, no expression was detected in the heart, lung, spleen, pancreas, and brain. The outcomes of our investigation propose the viability of LAP2 for gene therapy applications demanding the expression of large or multiple therapeutic genes following a single viral-vector administration.